2008
DOI: 10.17705/1cais.02305
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between E-Government and National Competitiveness: The Moderating Influence of Environmental Factors

Abstract: Using secondary data from 113 countries and the literature on Resource Based View [RBV] and Information Technology [IT] impact as the guiding theoretical lenses, we examine the relationships of e-government development and e-participation with national business competitiveness. E-government development represents the level of functional sophistication of e-government Web sites in a nation whereas e-participation is the level of country's willingness to engage citizens in e-government processes. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 66 publications
2
39
1
Order By: Relevance
“…For example, the study's results confirmed the importance of national resources (wealth, human capital, technological infrastructure, innovative capacity) and national governance institutions (rule of law, transparency), which other researchers have shown to positively influence the development, diffusion, and maturity of E-gov initiatives in TEDC and elsewhere (Kamarck & Nye, 2002;Kovačić, 2005;Wong & Welch, 2004;Moon et al, 2005;Katchanovski & La Porte, 2005;Siau & Long, 2006;Singh et al, 2007;Srivastava & Teo, 2008;Azad et al, 2010). Additionally, this current research complemented and advanced the study of Srivastava and Teo (2008) and Singh et al (2007) by testing the granular interaction effects of relevant environmental, contingent factors on the E-gov maturity variable. As such, this present research alongside those by Kubicek and Westholm (2005), Singh et al (2007) and Srivastava and Teo (2008) could inform a basis for a "contingency model of Egov maturity", which future research efforts could draw from and expand in discussing comparable issues.…”
Section: Implications For Researchsupporting
confidence: 60%
See 4 more Smart Citations
“…For example, the study's results confirmed the importance of national resources (wealth, human capital, technological infrastructure, innovative capacity) and national governance institutions (rule of law, transparency), which other researchers have shown to positively influence the development, diffusion, and maturity of E-gov initiatives in TEDC and elsewhere (Kamarck & Nye, 2002;Kovačić, 2005;Wong & Welch, 2004;Moon et al, 2005;Katchanovski & La Porte, 2005;Siau & Long, 2006;Singh et al, 2007;Srivastava & Teo, 2008;Azad et al, 2010). Additionally, this current research complemented and advanced the study of Srivastava and Teo (2008) and Singh et al (2007) by testing the granular interaction effects of relevant environmental, contingent factors on the E-gov maturity variable. As such, this present research alongside those by Kubicek and Westholm (2005), Singh et al (2007) and Srivastava and Teo (2008) could inform a basis for a "contingency model of Egov maturity", which future research efforts could draw from and expand in discussing comparable issues.…”
Section: Implications For Researchsupporting
confidence: 60%
“…Additionally, this current research complemented and advanced the study of Srivastava and Teo (2008) and Singh et al (2007) by testing the granular interaction effects of relevant environmental, contingent factors on the E-gov maturity variable. As such, this present research alongside those by Kubicek and Westholm (2005), Singh et al (2007) and Srivastava and Teo (2008) could inform a basis for a "contingency model of Egov maturity", which future research efforts could draw from and expand in discussing comparable issues. A study of the literature indicated that some recent E-gov research lacked solid theoretical foundations (e.g.…”
Section: Implications For Researchmentioning
confidence: 88%
See 3 more Smart Citations